2023
DOI: 10.1101/2023.03.07.531595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tld1 is a novel regulator of triglyceride lipolysis that demarcates a lipid droplet subpopulation

Abstract: Cells store lipids in the form of triglyceride (TG) and sterol-ester (SE) in lipid droplets (LDs). Distinct pools of LDs exist, but a pervasive question is how proteins localize to and convey functions to LD subsets. Here, we show the yeast protein Bsc2 localizes to a subset of TG-containing LDs, and reveal it negatively regulates TG lipolysis. Mechanistically, Bsc2 LD targeting requires TG, and LD targeting is mediated by hydrophobic regions (HRs). Molecular dynamics simulations reveal these Bsc2 HRs interact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
2
7
0
Order By: Relevance
“…This indicates that Pdr16 might limit lipolytic LD breakdown when lipids become more precious due to restrictions in nutrient availability, a function that may also apply for vegetative haploid cells exposed to glucose restriction. Consistently, Bsc2, a protein that we previously identified as a further resident of the LDO-and Pdr16-enriched LD subpopulation of cells in logarithmic growth phase (Eisenberg-Bord et al, 2018), was recently shown to counteract triacylglycerol lipolysis (Speer et al, 2023), suggesting that the LD subpopulation engaged in vCLIP during logarithmic phase might be protected from lipolysis. Similar to what we observe for metabolic regulation of vCLIP abundance, the pool of Bsc2-positive LDs expands when cells run out of glucose (Speer et al, 2023).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This indicates that Pdr16 might limit lipolytic LD breakdown when lipids become more precious due to restrictions in nutrient availability, a function that may also apply for vegetative haploid cells exposed to glucose restriction. Consistently, Bsc2, a protein that we previously identified as a further resident of the LDO-and Pdr16-enriched LD subpopulation of cells in logarithmic growth phase (Eisenberg-Bord et al, 2018), was recently shown to counteract triacylglycerol lipolysis (Speer et al, 2023), suggesting that the LD subpopulation engaged in vCLIP during logarithmic phase might be protected from lipolysis. Similar to what we observe for metabolic regulation of vCLIP abundance, the pool of Bsc2-positive LDs expands when cells run out of glucose (Speer et al, 2023).…”
Section: Discussionsupporting
confidence: 67%
“…Consistently, Bsc2, a protein that we previously identified as a further resident of the LDO-and Pdr16-enriched LD subpopulation of cells in logarithmic growth phase (Eisenberg-Bord et al, 2018), was recently shown to counteract triacylglycerol lipolysis (Speer et al, 2023), suggesting that the LD subpopulation engaged in vCLIP during logarithmic phase might be protected from lipolysis. Similar to what we observe for metabolic regulation of vCLIP abundance, the pool of Bsc2-positive LDs expands when cells run out of glucose (Speer et al, 2023). Collectively, this suggests that LDs engaged in vCLIPs may be preserved for longer-term lipid storage particularly during nutrient deprivation.…”
Section: Discussionsupporting
confidence: 67%
“…2B). These "voids," that in lipid bilayers are generated by the exposure of the hydrocarbon atoms belonging to the lipid acyl chains to the surface [22,73], affect LD surface properties [22] and, consequently, protein targeting [45,72,[74][75][76]. To this end, all-atom simulations have suggested that LPDs are possibly more persistent in LDs, compared with phospholipid bilayers [72,75], and, as such, can constitute specific binding sites for the preferential targeting of proteins [24,72].…”
Section: Ld-specific Protein Targetingmentioning
confidence: 99%
“…For instance, CYTOLD proteins have been proposed to bind to the monolayer following a multi-stage pathway: from their initial unfolded configuration in solution, proteins can fold upon anchoring to LPDs thanks to hydrophobic residues [72]. Indeed, specific sequence "signatures," in particular bulky hydrophobic residues, have been demonstrated by MD simulations to be crucial for specific binding to LDs [45,72,76].…”
Section: Ld-specific Protein Targetingmentioning
confidence: 99%
See 1 more Smart Citation